IN-HOSPITAL BLOOD PRESSURE VARIABILITY AS A PREDICTOR OF RENAL IMPAIRMENT IN PATIENTS WITH MYOCARDIAL INFARCTION: A 6-MONTH FOLLOW-UP STUDY. (June 2018) - Mantzouranis, M.; Tsioufis, K.; Dimitriadis, K.; Konstantinou, K.; Koumelli, A.; Fragoulis, C.; Kasiakogias, A.; Vogiatzakis, N.; Tousoulis, D.
Abstract : Objective: Recent data have associated blood pressure variability (BPV) with subclinical renal damage, acute renal injury and progression of chronic kidney disease but not in the setting of an acute coronary event. The aim of this study is to determine the impact of in-hospital short-term BPV on future renal impairment in patients suffering an acute myocardial infarction (AMI). Design and method: A total population of57 AMI patients [74.5% male; mean age: 67.56 years;75.4% hypertensives; 28.1% chronic kidney disease (GFR < 60 ml/min on admission)]underwent 24hr ambulatory BP measurement during their hospitalization. At 6months a follow-up was scheduled foreach patient in order to estimate their present renal function. Renal impairment was defined as a decline in GFR value between a discharge and a 6-month visit, which were calculated by using the Cockcroft-Gault Equation. In-hospital BPV was derived by assessment of standard deviation (SD), weighted-SD (SDw), average real variability (ARV) and coefficient of variability (CV). The study population was divided intoa STEMI group (n = 24) and a non-STEMI(n = 33) one. Results: After analysis of BPV indices, 6-month renal impairment was significantly associated with increased SBP CV[odds ratio, 0.467; CI, 0.218–1.003 (P = 0.051)]. This observation was met only in the STEMI group. A multinomial logistic regression analysiswas conducted for this group of patients, in which SBP CV demonstrated a significant prognostic role of renal impairment [odds ratio, 0.623; CI, 0.394–0.987 (P = 0.044)], independently of age, gender and24hr SBP. Conclusions: In the setting of STEMI, assessment of BPV using SBP CV has a prognostic role in the future development of renal dysfunction. This observation, if confirmed by further studies, could influence the therapeutic approach of ACS in terms of BP management.